2022
DOI: 10.1002/aur.2871
|View full text |Cite
|
Sign up to set email alerts
|

“Why do they do it?”: The short‐story task for measuring fiction‐based mentalizing in autistic and non‐autistic individuals

Abstract: This study aimed to validate the short‐story‐task (SST) based on Dodell‐Feder et al. as an instrument to quantify the ability of mentalizing and to differentiate between non‐autistic adults and autistic adults, who may have acquired rules to interpret the actions of non‐autistic individuals. Autistic (N = 32) and non‐autistic (N = 32) adult participants were asked to read “The End of Something” by Ernest Hemingway and to answer implicit and explicit mentalizing questions, and comprehension questions. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Additionally we evaluated it dichotomously; however, a more detailed description of reading experience could have provided a more comprehensive picture of the relationship between reading and ToM. Nevertheless, our results seem to be in line with the previously cited study, where the number of books read per month was used to assess reading experiences ( 38 ). In addition to quantity, a more detailed analysis would be interesting (e.g., regular reading vs. occasional reading, what genre they read, how characteristic reading was in different developmental periods, etc.).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Additionally we evaluated it dichotomously; however, a more detailed description of reading experience could have provided a more comprehensive picture of the relationship between reading and ToM. Nevertheless, our results seem to be in line with the previously cited study, where the number of books read per month was used to assess reading experiences ( 38 ). In addition to quantity, a more detailed analysis would be interesting (e.g., regular reading vs. occasional reading, what genre they read, how characteristic reading was in different developmental periods, etc.).…”
Section: Discussionsupporting
confidence: 85%
“…It seems reasonable to hypothesize that reading fiction may have a positive impact on ToM skills in subjects at risk of developing schizophrenia, or in patients already living with schizophrenia. This hypothesis is indirectly supported by the recent article mentioned, where the authors found that the number of books previously read predicted the SST performance in autistic and non-autistic individuals (38).…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations